Anisotropic Topological Surface States on High‐Index Bi2Se3 Films. (22nd January 2013) - Xu, Zhongjie; Guo, Xin; Yao, Mengyu; He, Hongtao; Miao, Lin; Jiao, Lu; Liu, Hongchao; Wang, Jiannong; Qian, Dong; Jia, Jinfeng; Ho, Wingkin; Xie, Maohai
<x xml:space="preserve">Abstract</x> A high‐index topological insulator thin film, Bi2Se3(221), is grown on a faceted InP(001) substrate by molecular‐beam epitaxy (see model in figure (a)). Angle‐resolved photoemission spectroscopy measurement reveals the Dirac cone structure of the surface states on such a surface (figure (b)). The Fermi surface is elliptical (figure (c)), suggesting an anisotropy along different crystallographic directions. Transport studies also reveal a strong anisotropy in Hall conductance. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>